Single-Stage Closing-Opening Wedge Osteotomy of Spine to Correct Severe Post-Tubercular Kyphotic Deformity of the Dorsal Spine - محفوض مفيد (Latakia University Journal -Medical Sciences Series, 2021)
The correction of severe post-tubercular kyphosis (PTK) is complex and has the disadvantage of being multiple staged with a high morbidity. The advent of effective antituberculous chemotherapy has largely made uncomplicated spinal tuberculosis a medical disease. Although complete disease cure may be achieved with chemotherapy, patients treated conservatively have an average increase of 15° in deformity and 3–5% of the patients end up with a deformity greater than 60°. We describe a closing–opening osteotomy for post-tubercular deformity that shortens the posterior column and opens the anterior column appropriately to correct the deformity without compromising the spinal cord. 35-year-old male who came to our clinic at hospital complained of Post-tuberculous kyphosis and was managed medically for two years. His symptoms were axial back pain which didn’t relieve by analgesics, with radicular pain along T7, T8 but there wasn’t neural damage and that resulted in cosmetic and psychological disturbance. Radiologic studies showed Kyphotic deformity and its apex located in T7, T8. Cobb Angle was 40. We decided to manage the case by Closing Posterior-Opening Anterior Wedge osteotomy (Posterior approach). Follow-up images showed a good axial and sagittal balance and kypohtic deformity was corrected. The patient started to walk after one week post-surgery. Single-stage closing opening wedge osteotomy is a reliable, effective and safe method to correct severe PTK.